2014
DOI: 10.1071/zo14068
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and the salivary gland response in free-ranging yellow-winged grasshoppers (Gastrimargus musicus)

Abstract: Yellow-winged grasshoppers (Gastrimargus musicus) were captured in the field to examine the morphology and amine immunohistochemistry of their salivary glands. Fifty-eight grasshoppers were collected, with only five being males. Eight of 53 female grasshoppers had food in their crop, and the salivary glands of those insects were significantly heavier than those of grasshoppers without food in their crops. The salivary gland of the yellow-winged grasshopper was an acinar-type gland, similar to gland description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The control of the cephalic labial gland lobes appears to be through a similar pathway as has been reported in other alveolar glands, as the presence of serotonin was consistent with that observed for cockroaches ( Baumann et al 2002 ), locusts ( Ali 1997 ), and yellow-winged grasshoppers ( Wahida and Cooper 2014 ). However, we cannot be certain that serotonin does stimulate fluid secretion within the cephalic lobes, as we have not performed that experiment.…”
Section: Discussionsupporting
confidence: 79%
“…The control of the cephalic labial gland lobes appears to be through a similar pathway as has been reported in other alveolar glands, as the presence of serotonin was consistent with that observed for cockroaches ( Baumann et al 2002 ), locusts ( Ali 1997 ), and yellow-winged grasshoppers ( Wahida and Cooper 2014 ). However, we cannot be certain that serotonin does stimulate fluid secretion within the cephalic lobes, as we have not performed that experiment.…”
Section: Discussionsupporting
confidence: 79%
“…We reported that the salivary glands of yellow-winged grasshoppers ( Gastrimargus musicus ) were reduced in size in insects that did not have food in the crop, but we could not distinguish whether this resulted from either not feeding or as a result of flight when the grasshoppers were caught [ 27 ]. The aim of this study is (1) to determine how starvation–feeding cycles might affect the morphology of the thoracic salivary gland of the cricket, Teleogryllus commodus , and (2) whether the amines serotonin or dopamine play a role in any gland changes by observing the effect of incubating semi-isolated glands of 72 h starved insects with amines, as well as measuring the concentration of these amines in starved and fed crickets.…”
Section: Introductionmentioning
confidence: 99%